Islamic marketing at the bottom of the pyramid: factors affecting customer’s satisfaction among the poor in Islamic pawnshop in Indonesia - Wulandari, Permata; Kassim, Salina (Inderscience Publishers, 2015)
This study attempts to investigate the service quality and its impact to customer satisfaction among the Islamic pawnshop borrowers in Indonesia. The psychometric properties of the well-known SERVQUAL model (reliability, assurance, tangibles, empathy, and responsiveness) and their relations with customer satisfaction are being used in this study. A field survey is being conducted among 300 Indonesian Islamic pawnshop borrowers in Jakarta, Bogor, Tanggerang and Bekasi (Jabodetabek) areas. Data were analysed using descriptive and regression analysis, namely the Pearson correlation analysis to identify the relationship between service quality dimensions to customer satisfaction, and the multiple regression analysis to determine the nature of each construct of service quality with customer satisfaction. The study finds that responsiveness has the biggest positive impact to customer satisfaction, while empathy has a negative impact to customer satisfaction unlike previous literature. Other constructs of service quality, namely reliability, assurance and tangibles have no significant impact to customer satisfaction. This study has significant contribution to the Islamic pawnshop operators in recognising the service quality dimensions that are important in establishing competition and maintaining sustainability of the Islamic pawnshops.